Exploring Significance of SPOC: A Path to Modernization of Music Cloud Computing - Li, Zhaoxia (EAI Endorsed Transactions on Scalable Information Systems, 2023)
INTRODUCTION: With the development of the information age and the application of cloud computing and big data technology, new changes have occurred in the field of education. Today, the form of learning is becoming more and more diversified, and cloud computing, big data and other information technologies can be more often applied in teaching and learning. The application of cloud computing to the creation and teaching of music can not only improve the interaction between teachers and students in the traditional classroom, but also cloud computing can better capture the problems of teaching in the classroom and provide adjustment suggestions through big data. OBJECTIVES: This study is to realize distance music teaching of SPOC through cloud computing, big data and other technologies. Further use of cloud computing technology is to improve the traditional music teaching classroom teaching and learning tools are not rich enough, the student perception is more single problem. At the same time, cloud computing technology is also utilized in order to explore the effect of distance music education. METHODS: Based on the management of learning theory, constructivism and communicative learning theory, this paper carries out the research on music creation and teaching through the methods of cloud computing and big data, and collects and summarizes the related literature at home and abroad, researches the development of big data and cloud computing in the field of music teaching and introduces the principle of SPOC teaching that supports students’ independent learning through big data technology. RESULTS: Based on the training concept of MOOC and cloud computing, the teaching process encourages teachers and students to apply the pedagogical methods of cloud computing to improve the level of music nowadays teaching and learning at the same time, improve the overall quality of students. CONCLUSION: Music aesthetics education has diversity, SPOC learning process and cloud computing technology should be developed by developing an independent learning method. Therefore, cloud computing technology can help students learn music independently in a three-dimensional way, effectively develop the design stage of the learning process, use big data and cloud computing to better enrich the music teaching model, and implement the construction of independent knowledge. Future research can continue to develop towards empirical evidence and a large number of data experiments.